2019
DOI: 10.1108/rausp-01-2019-0011
|View full text |Cite
|
Sign up to set email alerts
|

Islamic work ethics, organizational commitment and job satisfaction of Islamic banks in Indonesia

Abstract: Purpose This study aims to examine the relationship of the Islamic work ethics, organizational commitment and job satisfaction of Muslim employees in the four Islamic commercial banks in Indonesia. Design/methodology/approach The study has adopted a quantitative method with descriptive and inferential statistical analysis. A stratified random sample of the executive management was taken, proportionate to the size of each organization. Out of a total of 250 distributed questionnaires, 220 respondents have res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 42 publications
(78 reference statements)
3
51
0
3
Order By: Relevance
“…Components of IWE i.e. fairness, ethics, kind-heartedness, and faith raise the intrinsic motivational level of individuals (Gheitani et al, 2019;Nasution & Rafiki, 2019) that reduce the negative inner emotions i.e. threat of ego, dislikeness of others.…”
Section: Islamic Work Ethics As Moderatormentioning
confidence: 99%
“…Components of IWE i.e. fairness, ethics, kind-heartedness, and faith raise the intrinsic motivational level of individuals (Gheitani et al, 2019;Nasution & Rafiki, 2019) that reduce the negative inner emotions i.e. threat of ego, dislikeness of others.…”
Section: Islamic Work Ethics As Moderatormentioning
confidence: 99%
“…According to Mahdzan et al (2017), the consumers perceive that the Islamic banking is only for Muslim, thus non-Muslims are reluctant to engage in Islamic banking services. Some of the consumers see that both conventional and Islamic banking products and services are similar; it is simply "Islamising" the concept to attract the Muslim market (Butt et al, 2011;El-Gmal, 2001;Nasution and Rafiki, 2019). Meanwhile, the Islamic banks face a low level of awareness and understanding toward Islamic banking principles, hence influencing the consumers' choice.…”
Section: Introductionmentioning
confidence: 99%
“…An initial indication of these relationships was proposed by Harinoto et al (2017) study which has found that work commitment effectively mediates the effect of Islamic work ethics on employee performance. Nasution & Rafiki (2019) added that one of the work commitment constructs which is organizational commitment proves significantly mediate the relationship between Islamic work ethic and job satisfaction. Thus, the higher level of satisfaction of the employee, the higher the degree of an employee to stay with their existing job will be.…”
Section: The Mediation Role Of Work Commitmentmentioning
confidence: 99%